Poverty and economic growth: a review - Škare, Marinko; Pržiklas Družeta, Romina (Technological and Economic Development of Economy, 2016)
The objective of this paper is to review and attempt a synthesis of the relevant literature on growth versus poverty, and to analyze the causal link between the two phenomena. Research issues that drive our study are: Does economic growth tend to “raise all boats” as Kuznets (1955) pointed out? What is the role of the pattern of growth in the process of development? Which factor must we consider in designing appropriate pro-poor growth policies? This paper finds considerable variation in the poverty–reducing effectiveness of growth across time and authors. Also, our analysis speaks in favour of the fact that as growth occurs poverty reduces, no matter the level of inequality. Identically, similar growth pattern has different effects on poverty reduction. We conclude that growth is good for poverty alleviation but it is not enough. The extent to which growth reduces poverty depends upon how we measure poverty, and upon absorptive capacity of the poor, the pace and pattern of growth. In times when the rich are getting richer and the poor are getting poorer, “trickle-down” effect becomes a scenario that need to be reviewed.